2003
DOI: 10.1007/s00464-002-9098-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a new self-expanding plastic stent for inoperable esophageal strictures

Abstract: Self-expanding Polyflex stents are safe and effective for inoperable esophageal strictures and have an acceptable technical success rate. Further experience, better selection criteria, and design improvements should improve results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 17 publications
1
42
1
2
Order By: Relevance
“…This is considerable higher than reported in other studies (18.7 to 20.5%) [15,18]. However, in these studies patients with strictures or malignant stenosis were included.…”
Section: Discussioncontrasting
confidence: 53%
“…This is considerable higher than reported in other studies (18.7 to 20.5%) [15,18]. However, in these studies patients with strictures or malignant stenosis were included.…”
Section: Discussioncontrasting
confidence: 53%
“…Costamagna et al [18] have suggested that Polyflex stents are less expensive than expandable metal stents. Data on charges from our institution, however, indicate that current charges for all sizes of Polyflex stents are $2,775, compared with the Ultraflex metallic stent, which varies in cost from $1,825 to $2,183.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantages offered by this new generation of expandable plastic stents include decreased rate of tissue ingrowth, new stricture formation and increased levels of radial expansion that potentially decrease the need for dilation at the time of insertion, and the possibility of elective removal [14][15][16][17][18][19][20]. Experience with these stents in benign conditions is limited.…”
mentioning
confidence: 96%
“…More recently removable self-expanding silicone stents have been utilized. The efficacy of self-expanding silicone stents in relieving dysphagia has been demonstrated in patients with unresectable esophageal cancer [57][58][59], but they are also an attractive option for patients in the neoadjuvant setting because they can be removed at the time of resection or once chemoradiation has resolved the tumor mass.…”
Section: Stentingmentioning
confidence: 99%